2013
DOI: 10.1002/sca.21107
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on the measurement and use of the topography of the indentation imprint

Abstract: The goal of this paper is to study the main uses of the residual imprint of the indentation test. It also discusses the different technologies and methods employed in this context. The difficulties encountered when trying to exploit the full potentials of the imprint are thoroughly examined. A survey of the literature on the quantification of the pile-up clearly shows that there is a lack of consensus on the measurement of the residual imprint as well as on treatment methods. Therefore, in order to widen the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The hardness can be determined from a measurement of both the load, P and the contact stiffness, S. Zhou et al [27] as well as Saha and Nix [28] used a Berkovich indenter in their experiments. Finally, the large review of experimental techniques for the examination of residual imprints was presented in [29]. The authors have concluded that there is a lack of consensus on the methods used to study (analyse) residual imprints generated in the indentation tests.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness can be determined from a measurement of both the load, P and the contact stiffness, S. Zhou et al [27] as well as Saha and Nix [28] used a Berkovich indenter in their experiments. Finally, the large review of experimental techniques for the examination of residual imprints was presented in [29]. The authors have concluded that there is a lack of consensus on the methods used to study (analyse) residual imprints generated in the indentation tests.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, only the techniques based on altitude images can be used with ITSPM and there is a need for new methods as very recently reviewed 3 by Marteau et al [6]. This article introduces a new post mortem procedure that relies only on the altitude image and that is therefore valid for most types of SPM images, including ITSPM.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, Jae-il Jang et al [23] measured the impression size directly from scanning electron microscope (SEM) images of imprint and obtained the projected contact area which was treated as a triangle. Till now, the lack of consensus on the measurement of the residual imprint as well as treatment methods is also a severe problem hindering the research progress [24]. Recently, L. Charleux et al [25] introduced a postmortem procedure (LC method) that relies only on the height image and is therefore valid for most types of scanning probe microscope (SPM) image.…”
Section: Introductionmentioning
confidence: 98%